Distinct aetiopathogenesis in subgroups of functional dyspepsia according to the Rome III criteria. Issue 10 (18th November 2014) - Fang, Yu-Jen; Liou, Jyh-Ming; Chen, Chieh-Chang; Lee, Ji-Yuh; Hsu, Yao-Chun; Chen, Mei-Jyh; Tseng, Ping-Huei; Chen, Chien-Chuan; Chang, Chi-Yang; Yang, Tsung-Hua; Chang, Wen-Hsiung; Wu, Jeng-Yi; et al.
Abstract : Background and objective: Whether there is distinct pathogenesis in subgroups of functional dyspepsia (FD), the postprandial distress syndrome (PDS) and epigastric pain syndrome (EPS) remains controversial. We aimed to identify the risk factors of FD and its subgroups in the Chinese population. Methods: Patients with dyspepsia and healthy subjects who underwent gastric cancer screening were enrolled in this multicentre study from 2010 to 2012. All patients were evaluated by questionnaire, oesophagoduodenoscopy, histological examination and Helicobacter pylori tests. Subgroups of FD were classified according to the Rome III criteria. Psychiatric stress was assessed by the short form Brief Symptom Rating Scale. CagA and VacA genotypes were determined by PCR. Results: Of 2378 patients screened for eligibility, 771 and 491 fulfilled the diagnostic criteria of uninvestigated dyspepsia and FD, respectively. 298 (60.7%) and 353 (71.9%) individuals were diagnosed with EPS and PDS, respectively, whereas 169 (34.4%) had the overlap syndrome. As compared with 1031 healthy controls, PDS and EPS shared some common risk factors, including younger age (OR 0.95; 99.5% CI 0.93 to 0.98), non-steroidal anti-inflammatory drugs (OR 6.60; 99.5% CI 3.13 to 13.90), anxiety (OR 3.41; 99.5% CI 2.01 to 5.77) and concomitant IBS (OR 6.89; 99.5% CI 3.41 to 13.94). By contrast, H. pylori (OR 1.86; 99.5% CI 1.01 to 3.45), unmarried status (OR 4.22; 99.5% CI 2.02 to 8.81), sleep disturbance (OR 2.56; 99.5% CI 1.29 to 5.07) and depression (OR 2.34; 99.5% CI 1.04 to 5.36) were associated with PDS. Moderate to severe antral atrophy and CagA positive strains were also more prevalent in PDS. Conclusions: Different risk factors exist among FD subgroups based on the Rome III criteria, indicating distinct aetiopathogenesis of the subdivisions that may necessitate different therapeutic strategies.